Introduction to physical geography - Strahler, Arthur Newell (John Wiley & Sons, Inc, 1970)
New material includes separate chapters for servey of the earth's atmosphere as a layered structure and the heating and cooling of the atmosphere as viewed from the standpoint of a global radiation budget. New world maps of surface air temperatures, pressures, and winds are a major improvement,...